Balloon-augmented Onyx endovascular ligation: initial human experience and comparison with coil ligation. (26th May 2014) - Osanai, Toshiya; Bain, Mark D; Toth, Gabor; Hussain, M Shazam; Hui, Ferdinand K
Abstract : Introduction: Carotid artery sacrifice remains an important procedure for cerebral vascular disorders despite the development of new endovascular devices. Conventional carotid artery sacrifice with detachable coils alone often requires numerous coils to complete occlusion. Objective: To describe the initial human experience with balloon-augmented Onyx and coil vessel sacrifice based on our previous experience with animals. Methods: We performed a retrospective review of patients who underwent carotid artery sacrifice between 2008 and 2012 in accordance with local investigational review board approval. Two methods were used to occlude carotid arteries—namely, combined Onyx and coil embolization and traditional coil embolization. We compared the two methods for the cost of embolizate, time to occlude the vessels, and the number of coils. Results: Eight consecutive patients (combined group n=3, traditional group n=5) were assessed. The median cost of embolic material was $6321 in the combined Onyx and coil embolization group and $29 996 in the traditional coil embolization group. The median time from first coil placement to achievement of vessel occlusion was 52 min in the Onyx group and 113 min in the coil embolization group. The median number of coils used was 4 in the Onyx group and 35 in the coil embolization group (p<0.05). No symptomatic complications or recurrences were seen in the combined group. Conclusions: Balloon-augmented Onyx endovascular ligation may reduce costs and fluoroscopy times during vessel sacrifice. Further studies in a larger number of patients are needed to confirm these findings.